Numerical simulation and experimental verification on downwash air flow of six-rotor agricultural unmanned aerial vehicle in hover - Fengbo, Yang; Xinyu, Xue; Ling, Zhang; Zhu, Sun (International Journal of Agricultural and Biological Engineering, 2017)
Recently, multi-rotor unmanned aerial vehicle (UAV) becomes more and more significantly irreplaceable in the field of plant protection against diseases, pests and weeds of crops. The easy takeoff and landing performance, hover function and high spraying efficiency of UAV are urgently required to spray pesticide for crop timely and effectively, especially in dispersed plots and hilly mountains. In such situations, the current researches about UAV spray application mainly focus on studying the influence of the UAV spraying parameters on the droplet deposition, such as operation height, operation velocity and wind velocity. The deposition and distribution of pesticide droplets on crops which depends on installation position of nozzle and airflow distribution characteristics of UAV are directly related to the control effect of pesticide and crop growth in different growth periods. As a preliminary step, this study focuses on the dynamic development law and distribution characteristics of the downwash air flow for the SLK-5 six-rotor agricultural UAV. Based on compressible Reynolds-averaged Navier-Stokes (RANS) equations with an RNG k-ε turbulence model and dynamic mesh technology, the efficient three-dimensional computational fluid dynamics (CFD) method was established to analyze the flow field distribution characteristics of UAV in hover. Then the unsteady interaction flow field of the wing was investigated in detail. The downwash wind speed of the marked points for the SLK-5 UAV in hover was also tested by weather tracker. It was found that the maximum velocity value of the downwash flow was close to 10 m/s; the z-direction velocity was the main body of the wind velocity in the downwash airflow, and the comparison of the wind velocity experiment test and simulation showed that the relative error was less than 12% between the experimental and simulated values of the z-direction velocity at the marked points. Then the flow characteristics of the longitudinal and cross section were analyzed in detail, the results obtained can be used as a reference for drift and sedimentation studies for multi-rotor unmanned aerial vehicle.Keywords: UAV, downwash air flow, numerical simulation, experimental verification, pesticide spray, wing interferenceDOI: 10.25165/j.ijabe.20171004.3077Citation: Yang F B, Xue X Y, Zhang L, Sun Z. Numerical simulation and experimental verification on downwash air flow of six-rotor agricultural unmanned aerial vehicle in hover. Int J Agric & Biol Eng, 2017; 10(4): 41–53.